Challenges Affecting Strategy Implementation at the Food Reserve Agency in Zambia - Mazhambe, Zivanai; Mukololo, Musiwa (Journal of Public Administration and Governance, 2024)
The purpose of this study was to conduct an examination of the challenges affecting the implementation of strategies at the Food Reserve Agency (FRA) in Zambia. The study utilized an explanatory sequential mixed method design and involved data collection from 58 management employees selected through stratified and simple random sampling, as well as four key informants selected purposively. The research utilized a survey questionnaire and semi-structured interview guide for data collection. Descriptive statistics was used to analyse quantitative data in SPSS version 26, while N-vivo 12 was utilized to analyse the qualitative data through content analysis. The study’s results indicate that FRA faces various internal and external challenges that limit its ability to implement strategies successfully. These challenges comprise government funding, policy/political factors, stakeholders, environmental factors, economic factors, technological factors, disease outbreaks, industrial competition, legal factors, and social factors. Among these challenges, lack of financial resources was the most significant internal challenge encountered during strategy implementation at FRA.